THE PROBLEM OF REGULATING THE MARKET OF COLLECTIVE INVESTMENTS IN RUSSIA IN CONDITIONS OF FINANCIAL CRISIS - N. Redko (Модернизация, инновация, развитие)
At the moment the Bank of Russia became the megaregulator of the fi nancial market of Russia that opens new opportunities and prospects for development on the one hand, with another - there is a full monopolization of control and supervision of its participants. The author of article describes actual problems of regulation of the market of collective investments, relying on the existing practice of activity of management companies. Analyzing a situation from the point of view of protection of interests of the investor, and also for development of this sector of economy he suggests to shift focus in regulation. The main attention, in his opinion, needs to be turned on involvement of the experts conducting practicians and analysts in the sphere of professional and trust management for development of optimal solutions of the existing problems of the fi nancial market, and also for creation of the transparent and healthy economic environment of his activity. Aiming efforts at the development of innovative instruments of collective investment, it is possible to make signifi cant progress in overcoming of the crisis phenomena in fi nancial sector of economy